Trade warfare and regional integration in the Pacific : the USA, Japan and the Asian NICs. - BELLO, Walden (1994)
Discusses two approaches to regional hegemony in East Asia : integration via an aggressive trade policy pushed by the United States, and integration via a strategic investment policy followed by Japan.